Revitalizing Ki Hadjar Dewantara’s Philosophy in the Context of 21st Century Education Reform - Suyono; Rejokirono; Welius Purbonuswanto; Sigit Haryanto (Jurnal Penelitian Pendidikan IPA, 2026)
Indonesian education is increasingly shaped by digitalization and global benchmarks, producing an emphasis on cognitive performance while cultural and moral formation receives limited space, creating a need to reassess Ki Hadjar Dewantara's humanistic philosophy in relation to current policy. This study aims to analyze how Dewantara's key educational principles correspond to the objectives of the National Education System Law (Law No. 20/2003) and to identify the forms of tension that arise when these values are implemented in 21st-century schooling. A qualitative approach was employed through document analysis of Dewantara's texts and the National Education Law, supported by in-depth interviews with 10 key informants (teachers, school leaders, and education experts) and non-participant observation in two Taman Siswa schools in Yogyakarta and Semarang. The findings show substantive alignment between Dewantara's emphasis on moral character, learner autonomy, and contextual learning and the mandates of Article 3 regarding holistic development. However, autonomy is reduced in practice to scheduling flexibility, while bureaucratic reporting and centralized curriculum controls restrict creative pedagogy. Field observations also show that cultural-arts learning still contributes to character formation but is difficult to institutionalize under efficiency-driven policy incentives. The study concludes that harmony at the philosophical level does not ensure operational freedom, institutional reform through reduced administrative burden, greater school-level discretion, and cultural-based instruction is necessary to revitalize Dewantara's values in contemporary policy implementation